Poverty, Growth, and Inequality in Thailand - Anil B. Deolalikar (Asian Development Bank (ADB), 2002)
"A number of empirical studies using cross-country data have found that poverty incidence responds very strongly to economic growth. This paper explores the impact of economic growth as well as changes in income inequality on poverty reduction using provincial data from Thailand over the period 1992-1999. The results suggest that, while income growth has a strong positive effect on poverty reduction, income inequality has a sharply negative effect. Income inequality reduces the rate of poverty reduction in two ways: first, increased inequality is associated with increased poverty after controlling for economic growth, and second, high levels of initial inequality reduce future growth rates, thereby impeding the poverty reduction that would have taken place in the presence of rapid growth. What this suggests is that income inequality can play a critical role in affecting the rate of poverty reduction, especially in a low-growth environment. Given that near-term prospects for growth in Thailand are guarded, it may be particularly important for poverty reduction policies in that country to focus on improving income inequality, or at least preventing a further worsening of income inequality."
hdl:11540/1925
Keywords: 330; Armut; Armutsbekämpfung; Wirtschaftswachstum; Einkommensverteilung; Thailand